2013
DOI: 10.1158/1541-7786.mcr-13-0002-t
|View full text |Cite
|
Sign up to set email alerts
|

miR-150 Blocks MLL-AF9–Associated Leukemia through Oncogene Repression

Abstract: The microRNA miR-150, a critical regulator of hematopoiesis, is downregulated in mixed-lineage leukemia (MLL). In this study, miR-150 acts as a potent leukemic tumor suppressor by blocking the oncogenic properties of leukemic cells. By using MLL-AF9-transformed cells, we demonstrate that ectopic expression of miR-150 inhibits blast colony formation, cell growth, and increases apoptosis in vitro. More importantly, ectopic expression of miR-150 in MLL-AF9-transformed cells completely blocked the development of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Recent work has shown that KLF4 is an important transcription factor whose expression is low or absent in AML cases with high CDX2 expression (16) and that the loss of miR-150 expression leads to increased proliferation, decreased apoptosis, and inhibited differentiation in AML (22)(23)(24). Our work now demonstrates that KLF4 expression is decreased in a large proportion of AML cases irrespective of most cytogenetic abnormalities.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recent work has shown that KLF4 is an important transcription factor whose expression is low or absent in AML cases with high CDX2 expression (16) and that the loss of miR-150 expression leads to increased proliferation, decreased apoptosis, and inhibited differentiation in AML (22)(23)(24). Our work now demonstrates that KLF4 expression is decreased in a large proportion of AML cases irrespective of most cytogenetic abnormalities.…”
Section: Discussionsupporting
confidence: 61%
“…Previously, we showed that miRNA 150 (miR-150) expression is low or absent in pediatric and adult AML patient samples across various cytogenetic and molecular risk groups and in normalkaryotype (NK) AML cases, suggesting that miR-150 loss occurs pervasively in AML (22)(23)(24). In AML primary patient samples and cell lines, we demonstrated that expression of miR-150 decreases cell proliferation and promotes myeloid differentiation (22).…”
mentioning
confidence: 93%
“…Genes crucial for lactation, such as miR-150-5p predicted targets Elovl5 and Fads1, are expressed at low levels until late pregnancy when they increase coincident with the decline of miR-150-5p. Conversely, validated miR-150 targets Egr2 (Bousquet et al, 2013) and Myb (Xiao et al, 2007) decreased at mid-pregnancy when miR-150 increased (Fig. S2B).…”
Section: Decreased Expression Of Mirnas Between Late Pregnancy and Eamentioning
confidence: 96%
“…This event is due to myeloproliferation and decrease of erythropoiesis. SHIP1 downregulation results in activation of IL-6 signaling pathway and induces a reactive proliferation of the relatively apoptosis-resistant myeloid precursor cells [49,73]. …”
Section: Mirna-29mentioning
confidence: 99%
“…Group 1 characterized with high level of expression of sncRNAs, which associated with sensitivity to therapy. This group members are miRNA-181a, b; let-7f, miRNA-9*, miRNA-96, miRNA-135a, miRNA-409, miRNA-10, miRNA29b and miRNA-217 [72,73,[97][98][99][100]. Group 1 members act through activation of cellular differentiation, inhibition of leukemic cells proliferation and survival, regulation of cell cycle, inducing of apoptosis and suppression of migration and invasion.…”
Section: Sncrnas As Markers Of Therapeutic Resistance or Sensitivity mentioning
confidence: 99%